Bahasa sebagai asas jati diri bangsa: isu, cabaran dan upaya pelestariannya (Jurnal Bahasa, 2007)
This article focuses on the issue of the relation between language and identity of a nation, with special reference to the Malay language. The primaiy premise in discussing the relation is the fact that language, together with mind, is an important characteristic and property of mankind, which differentiates man from animal and the others. Religious and scientific evidences are consulted in discussing this issue. In the context of the Malay language, this article traces the development of the language as a tool of civilizational progress in all fields of life among the people in the Malay Archipelago, since the early time, especially in the time of Sriwijaya and the Malay Sultanates. The last part of the article refers to the current situation of Malay in the context of nation building, the crisis of identity and some suggestions to strengthen Malay in facing contemporary and future challenges.